La resemantización del archivo religioso: un nexo entre Clarice Lispector y Silvina Ocampo (Dossier Literatura brasileña y latinoamericana: cruce de lecturas) - Saade, Ignacio (2025)
This article aims to study the meaning-making operations carried out by Clarice Lispector in The Via Crucis of the Body and Silvina Ocampo in The Sibyl, The Mortal Sin, and The Invited Women, through the insertion of various elements from the realm of sexuality into Christian discourse. We explore the idea that the narrative strategies deployed by these authors disrupt the emanations of the religious archive and enable a potential resemantization of words traditionally associated with dogma. First, we examine the implications and components involved in the clash between eroticism and religion. Then, we turn to the issue of naming and the parodic resignifications of the biblical archive. Lastly, focusing on the corporeal sphere, we analyze how the authors connect their characters’ bodies to this thematic framework and what attributes they assign to them.